Inuit Students' Journeys from High School into Post-Secondary Education - Ochalski, Heather (Université d'Ottawa / University of Ottawa, 2021)
Education is a critical social process and is the responsibility of the society of which a child is a member. Education and Schooling promote the cognitive development and professional skills acquisition that produce economic development and positive socio-economic outcomes. In the modern world, education is strongly correlated with employability, access to food, housing, social status and associates strongly with measures of individual health and wellbeing. However, despite moderate gains in education outcomes for Inuit students, school engagement and graduation rates remain low across Inuit Nunangat in the K-12 system, and entry into post-secondary education has increasingly lagged behind that of the rest of Canadians. All the while, Inuit remain the most socio-economically disadvantaged people in Canada. At the root of this education gap is the collision of two cultures and world views. In the last sixty-five years (roughly just two generations), Inuit non-monetary social and economic systems, as well as teaching methods, have been eroded and replaced by dominant Western pedagogical and economic practices. This has caused tension between Inuit and Western pedagogy and provoked re-examination of what gets taught in the dominant Western education system in order to prepare Inuit students to participate in Canadian society. This study narrates the experiences of six Inuit students' education journeys and explores how they navigated cultural tensions to successfully reach and complete their post-secondary education. Findings indicate that the presence of Inuit Qaujimajatuqangit (Inuit epistemology), or rather its prescriptive Guiding Principles (the branch of Inuit social epistemology) when practiced, supported their success. Further, the lack of these Principles, evident in microaggressions from educators, segregation, racism, suicides, and lateral violence from peers all served as barriers to their educational goals of being able to participate bi-culturally in both the Inuit and Western ways of living.